2013
DOI: 10.3389/fbioe.2013.00015
|View full text |Cite
|
Sign up to set email alerts
|

Why Most Traumatic Brain Injuries are Not Caused by Linear Acceleration but Skull Fractures are

Abstract: Injury statistics have found the most common accident situation to be an oblique impact. An oblique impact will give rise to both linear and rotational head kinematics. The human brain is most sensitive to rotational motion. The bulk modulus of brain tissue is roughly five to six orders of magnitude larger than the shear modulus so that for a given impact it tends to deform predominantly in shear. This gives a large sensitivity of the strain in the brain to rotational loading and a small sensitivity to linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
85
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 32 publications
1
85
1
2
Order By: Relevance
“…Rotational acceleration however, showed more significant differences between the helmet models which suggests that this metric might be the most sensitive to changes in helmet designs. This is also pertinent as rotational acceleration has often been suggested as an important contributor to the occurrence of concussion (Gennarelli et al, 1987;Kleiven, 2013;Lamy et al, 2013). The fact that maximum principal strain does not distinguish in many cases between the helmets might be a result of the combination of linear and rotational acceleration for these impacts causing a very similar amount of strain in the brain, and thus masking helmet designs that would reduce one type of motion over the other.…”
Section: Helmet Analysismentioning
confidence: 99%
“…Rotational acceleration however, showed more significant differences between the helmet models which suggests that this metric might be the most sensitive to changes in helmet designs. This is also pertinent as rotational acceleration has often been suggested as an important contributor to the occurrence of concussion (Gennarelli et al, 1987;Kleiven, 2013;Lamy et al, 2013). The fact that maximum principal strain does not distinguish in many cases between the helmets might be a result of the combination of linear and rotational acceleration for these impacts causing a very similar amount of strain in the brain, and thus masking helmet designs that would reduce one type of motion over the other.…”
Section: Helmet Analysismentioning
confidence: 99%
“…31,69,73 In nature, linear and rotational acceleration seldom exist independent of each other 21,50 and, as such, both forms of loading have been shown to contribute to head injury. 55 Skull fractures have been more commonly associated with linear acceleration 33,47 whereas rotational kinematics are more commonly associated with concussion and other forms of TBI. 17,21,56,74 Additionally, research examining the cause of concussion in the National Hockey League (NHL) reported concussive events due to falls account for only 7% of all concussions while collisions with an opponent accounted for 88%.…”
Section: Introductionmentioning
confidence: 99%
“…24 These accelerations result in transient pressure gradients and strain fields within the soft tissue of the brain. 25 If the pressure gradients or strains exceed the tolerable limits of the brain tissue, injury occurs.…”
mentioning
confidence: 99%
“…25 Whereas debate exists about whether resultant LA, resultant AA, or combined resultant LA and AA influence concussion risk, 32,33 they likely do not occur in isolation. 24 In addition to simple magnitudes, impact-severity measures quantify injury tolerance, and the original work in car impacts yielded the Wayne State Tolerance Curve (WSTC). 34 The objective of the WSTC was to inform protective material development by understanding the risk of skull fracture in moderate and severe TBI.…”
mentioning
confidence: 99%